Spatiotemporal consistency of trajectories in gymnastics: A three-dimensional analysis of Flic-Flac - Grassi, G. -P.; Santini, T.; Lovecchio, N.; Turci, M.; Ferrario, V. F.; Sforza, C. (International Journal of Sports Medicine, 2005)
Sport performance during the execution of closed skills combines specific body and limb movements into codified patterns where stability and consistency may be more important than variability. Repeated sport movements can be investigated to assess the consistency of body trajectories. More consistent trajectories will result in more repeatable movements. The present study quantified the short-term consistency of body trajectories during the performance of the backward flic-flac, a technique of floor gymnastics. Nine experienced gymnasts (six men, three women), all of national level, performed 10 repetitions of backward flic-flac. An optoelectronic instrument was used for the detection of the three-dimensional movement of 13 body landmarks. The spatiotemporal consistency of repeated landmark trajectories was measured by the standard deviation between standardized trajectories. The results showed smaller standard deviation (larger consistency between landmark trajectories) in female than in male gymnasts. The analysis of the consistency of landmark trajectories could help gymnasts indicating which parts of the body do not repeat a selected movement with sufficient accuracy.